Radiotherapy for Pediatric Malignancies: An Experience from a Tertiary Cancer Centre - Vinin, NV; Jones, Joneetha; Jithin, TK; Gopakumar, KG; Geethanjali, A; Muttath, Geetha (Asian Pacific Journal of Cancer Care, 2022)
Background: Incidences of pediatric malignancies are increasing. In management of various childhood malignancies like hematological, bone and soft tissue tumors radiotherapy plays a crucial role. RT treatment planning and delivery poses a challenge to clinicians. Hence with this study we wanted to know the radiotherapy practices in our institution. Materials and Methods: This was a retrospective study analyzing case records and RT charts of all pediatric malignancies who received radiation treatment for a period of 3 years from January 2018 to December 2021. Demographic details, RT details, toxicity details were carefully recorded. Results: Details of 73 pediatric malignancy cases who received RT were analyzed. Median age was 10 years and the majority were males (66%). Commonest malignancies which received RT treatment were ALL (30%), Brain tumors (26%) and bone and soft tissue tumors (22%). Radiotherapy was given as a part of radical intent treatment including neo adjuvant, definitive, adjuvant and prophylactic in 92% of patients. Conformal RT techniques in the form of 3DCRT and VMAT were used in majority (91%) cases. A significant proportion (27%) of cases required anesthesia for RT treatment delivery. 16% of patients had treatment break and common reasons for treatment break being infections (COVID, respiratory) and neutropenia. Grade 3 or more acute toxicities were observed in 14% of patients and hematological toxicity was the most frequent. Conclusion: Hematological and bone & soft tissue tumors are the most common pediatric malignancies requiring RT as a part of multimodality treatment. For RT treatment delivery anesthesia services may be required in pediatric malignancies. Acute Grade 3 or more toxicities and treatment breaks are a concern and these pediatric cases require a properly coordinated supportive care during treatment.